The Phonological Errors by Dutch Exchange Students in Reading Indonesian Texts - Henny Putri Saking Wijaya; Yohanes Theodorus Mustamu (kata, 2017)
In this study, the five non-existing Indonesian sounds in Dutch sound system was observed because these sounds cause a problem. Moreover, the writers analyzed the phonological errors produced by the Dutch exchange students. The theories were from Moeliono and Darwowidjojo (2003) for the Indonesian consonants and from Mennen, Levelt and Gerrits (2006) for the Dutch consonants. The findings show that there were five Indonesian sounds that do not exist in Dutch sound system. Furthermore, the Dutch exchange students produced phonological errors in initial, medial and final positions. Also, from the observed sounds, thirteen deviations occurred. In conclusion, the phonological errors in five observed sounds produced by the Dutch exchange students happened because of the L1 transfer and the lack of knowledge of Indonesian consonants.